Three Replicons of Rhizobium sp. Strain NGR234 Harbor Symbiotic Gene Sequences - Flores, Margarita (American Society for Microbiology, 1998)
Rhizobium sp. strain NGR234 contains three replicons: the symbiotic plasmid or pNGR234a, a megaplasmid (pNGR234b), and the chromosome. Symbiotic gene sequences not present in pNGR234a were analyzed by hybridization. DNA sequences homologous to the genes fixLJKNOPQGHIS were found on the chromosome, while sequences homologous to nodPQ and exoBDFLK were found on pNGR234b.